Dynamic 19F-MRI of pulmonary ventilation in lung transplant recipients with and without chronic lung allograft dysfunction - Mary A. Neal, PhD; Saskia Bos, MD, PhD; Charlotte W. Holland, MRCP; Kieren G. Hollingsworth; Gerard Meachery, FRCP; Arun Nair, MD, FRCP; James L. Lordan, FRCP; Andrew J. Fisher, FRCP, PhD; Peter E. Thelwall, PhD (JHLT Open)
Background: By the time chronic lung allograft dysfunction (CLAD), with its main phenotypes bronchiolitis obliterans syndrome (BOS) and restrictive allograft syndrome (RAS), is diagnosed by pulmonary function testing, irreversible damage to the lung allograft may already have occurred. Dynamic 19F-MRI of inhaled perfluoropropane may detect subtle changes in regional lung ventilation and provides a quantitative measure of regional lung function. We assessed feasibility of detecting regional ventilation dysfunction due to CLAD in lung transplant recipients. Methods: Dynamic 19F-MRI was performed in ten lung transplant recipients, four without CLAD and six with CLAD (5 BOS, 1 RAS). Gas wash-in and washout dynamics were assessed and regional lung clearance index (RLCI) provided a quantitative metric of regional lung ventilation. Results: BOS patients had substantially greater variation in regional ventilation compared with stable patients, with more regions of reduced ventilation, especially in the periphery. Tracer washout was homogeneous and rapid in stable patients but highly heterogeneous in CLAD. CLAD patients exhibited significant difference in RLCI between central and peripheral lung regions (p = 0.0016) and a wider interquartile range of RLCI for wash-in compared with stable patients (no CLAD 4.1, BOS 10.5, p = 0.036). FEV1 (% of baseline) negatively correlated with ventilation during wash-in, most strongly for the periphery (r = −0.844, p = 0.0021). Conclusions: Dynamic 19F-MRI identified quantifiable differences in regional ventilation in lung transplant recipients with and without CLAD and was well tolerated. Larger longitudinal studies using this approach will determine if early detection of changes in regional ventilation in lung transplant patients allows earlier CLAD detection.